Vocational High School Female Students’ Opinions About Application Level of Skill Education - Gülçin ÜSTÜN; Duygu SAVAŞ (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
Vocational Education Law was put into practice in 1986 to make the execution of vocational education in accordance with the needs and demands of work life. Applications of this new skill education framework were developed quickly. However, examinations and evaluations on vocational education show that skill education practices running in enterprises were incomplete or incorrect. The purpose of this study is to analyze application level of the vocational education given in school/company and enterprises in accordance with Vocational Education Law. 138 senior level students from four different vocational high schools in Ankara were randomly selected and included in this study. Data were collected using survey and scanning methods. Statistical Package for Social Sciences (SPSS) was used to analyze data. Results show that participants were satisfied with the skill education given in enterprises. Data also suggested that an effective communication was needed between school and enterprises to be able to put new skill education requirements in order improving the quality of work force